The Religious Motivation of Cromwell’s Major-Generals - Fletcher, Anthony (Studies in church history, 1978)
When Oliver Cromwell sent his most trusted lieutenants into the provinces in 1655, the instructions he gave them were wide ranging and the task he set them was enormous. They were to oversee every aspect of local government, prevent conspiracies, remove negligent or scandalous ministers and promote godliness and virtue among the people. No wonder the major-generals felt daunted. John Thurloe, who as secretary-of-state handled their correspondence, soon found himself acting as a bureau for encouragement and advice. Once they were out on their own there was little to sustain the major-generals beyond their religious faith. This is not to say that their accounts of their doings should be taken wholly at face value, nor that baser motives were necessarily absent from their minds. It is hard to believe that any of the major-generals expected immediate material gain. But some at least may have been influenced by the search for power and the desire for revenge against their enemies in the civil war. Plainly, several of them still felt bitter hatred of cavaliers almost ten years after the war had ended. Such attitudes can be no more than glimpsed in letters designed to give a good impression of the major-generals’ performance. The motives that lay behind that performance must be assessed on the basis of what they wrote and the aspects of the CromweUian programme upon which they concentrated. The letters to Thurloe do much to explain why the major-generals worked so hard, riding the muddy lanes of England through a hard winter; they also illuminate the nature of their vision of a godly commonwealth.